ON SmBE-ALGEBRAS - Saeıd, A. Borumand; Rezaeı, A.; Kıa, O. Yousefı (Fırat University, 2015)
In this article, class of all bounded commutative self distributive modal BE-algebras SmBE is introduced. Finally, we show that the class of all bounded commutative self distributive modal BEalgebras, SmBE, coincides with the class of all topological Heyting algebras.